Characterisation of the main playing variables affecting the service in high-level women's volleyball - Quiroga, M. E.; Rodriguez-Ruiz, D.; Sarmiento, S.; Muchaga, L. F.; da Silva Grigoletto, M.; Garcia-Manso, J. M. (Journal of Quantitative Analysis in Sports, 2012)
This study sought to establish the most important factors affecting he service in high-level women`s volleyball and the relative weighting of such factors on this technical part of the sport. A total of 1300 services from eight matches played in two Final Fours of the Indesit European Champions League were analysed. The services were delivered by 58 players of 25 nationalities. Observation sheets and two video cameras located at both ends of the court were used. Service speed was measured by radar. The twelve variables studied enabled the service to be divided into four components. The most influential component (19.02% of total variance) comprised variables related to technical service characteristics (type of service and service speed). The second most influential component (15.16% of variance) was related to the opponents` technique and tactics, and to their position on court at the time of the service. The service was also affected by the technical and tactical movements that the servicer needed to perform in the subsequent play (12.20%). The stage of the match and the score (10.67%) also presented players with different levels of risk and helped to determine the type of service chosen and the power with which it was executed.